Case Report: The long-term effects of the empagliflozin therapy on glycemia and renal function in a patient with Rabson-Mendenhall syndrome caused by two heterozygous variants in INSR gene - Chrzanowska, Joanna; Lachowska, Julia; Weimann, Maja; Zubkiewicz-Kucharska, Agnieszka; Fornalczyk, Konstancja; Kilis-Pstrusińska, Katarzyna; Smigiel, Robert (Frontiers in Endocrinology, 2025)
We present a patient with Rabson-Mendenhall syndrome with unsatisfactory glycemic control of diabetes despite the use of metformin, pioglitazone, and sitagliptin. We investigated the long-term effects of treatment with an empagliflozin. After one year of empagliflozin therapy, an improvement in metabolic control of diabetes was detected. However, eleven months after implementation of empagliflozin, the patient was diagnosed with an early form of nephrocalcinosis. The empagliflozin dose was reduced, maintaining metabolic control and reducing hypercalciuria. We discuss the probable causes of nephrocalcinosis as well as the potential impact of SGLT-2 inhibitor therapy on the occurrence and progression of renal calcium deposition.